Maintenance of Homeostasis in the Aging Hypothalamus: The Central and Peripheral Roles of Succinate - Chen, Thomas T.; Maevsky, Eugene I.; Uchitel, Mikhail L. (Frontiers in Endocrinology, 2015)
Aging is the phenotype resulting from accumulation of genetic, cellular, and molecular damages. Many factors have been identified as either the cause or consequence of age-related decline in functions and repair mechanisms. The hypothalamus is the source and a target of many of these factors and hormones responsible for the overall homeostasis in the body. With advanced age, the sensitivity of the hypothalamus to various feedback signals begins to decline. In recent years, several aging-related genes have been identified and their signaling pathways elucidated. These gene products include mTOR, IKK-β/NF-κB complex, and HIF-1α, an important cellular survival signal. All of these activators/modulators of the aging process have also been identified in the hypothalamus and shown to play crucial roles in nutrient sensing, metabolic regulation, energy balance, reproductive function, and stress adaptation. This illustrates the central role of the hypothalamus in aging. Inside the mitochondria, succinate is one of the most prominent intermediates of the Krebs cycle. Succinate oxidation in mitochondria provides the most powerful energy output per unit time. Extra-mitochondrial succinate triggers a host of succinate receptor (SUCN1 or GPR91)-mediated signaling pathways in many peripheral tissues including the hypothalamus. One of the actions of succinate is to stabilize the hypoxia and cellular stress conditions by inducing the transcriptional regulator HIF-1α. Through these actions, it is hypothesized that succinate has the potential to restore the gradual but significant loss in functions associated with cellular senescence and systemic aging.